Raul Ruiz's Cinema of Inquiry (Book collections on Project MUSE., 2017)
Most widely known for his filmic productions, Raúl Ruiz (1941-2011) was a highly prolific, erudite, and innovative artist, whose work is located at the intersection of diverse locations, languages, and aesthetic traditions. Ruiz's eclectic body of work includes over one hundred films (among them features, shorts, television serials, and videos), books on the theory of cinema, genre-defying fiction books, plays, a radio show, and a multimedia installation. Raúl Ruiz's Cinema of Inquiry posits the unity of Ruiz's body of work and investigates the similarities between his very diverse artistic productions. Ruiz's own concept of'cinema of inquiry'provides the lens through which his films and poetics are examined. Ruiz's relevance to cinema and the growing interest in his work are due to his legacy as a global filmmaker. Viewers, filmmakers, and film scholars continue to return to his works because his films consistently pose the question of what cinema can be, especially at a time when cinema is increasingly seen as displaced by television and new media. Ruiz expanded the domain of cinema itself, incessantly probing the interstices between cinema and other arts. Editors Ignacio López-Vicuña and Andreea Marinescu, with six other scholars, explore different aspects of Ruiz's work, with special attention paid to the transnational aspects of Ruiz's films, critical regionalism, and political and aesthetic interventions. Raúl Ruiz's Cinema of Inquiry includes close readings of important yet understudied films, as well as two extensive previously unpublished interviews with Ruiz. This comprehensive volume gives voice to a significant filmmaker and artist. Students and scholars of film and media studies will find great value in this collection.